Factors affecting Financing Decision of Indian Power & Energy Sector and Testing of Capital Structure Theories: Panel Data Analysis - Rajesh Desai (Universitas Trisakti, 2020)
Capital structure (CS) is defined as combination of various sources of funds employed in business. Appropriate source of financing is inevitable for any company to exist. Present paper analyses the determinants affecting the choice of debt or equity of selected power and energy sector companies of India. For the purpose of empirical testing, panel data of 25 listed companies has been collected for 10 years (2010-2019). Based on panel regression model, the study concludes that profitability, tangibility, liquidity, non-debt tax shield, and interest coverage ratio are major determinants of CS choice of selected companies. In addition to this, study also validate the applicability of CS theories in Indian set up and concludes that power & energy companies follow the propositions of pecking order and trade-off theory. The findings of the paper will be useful to managers as it portrays critical factors affecting the CS and analysing their impact on financing decision. It will also enrich the existing pool of research in the area of capital structure and bridge the gap in existing research.